Glycemic control and lipid profile of diabetic defaulters in Kuantan, Malaysia - Abdullah, Fa’iza; Tin, Myo Han; Md Aris, Mohd Aznan; Osman, Iskandar Firzada (2017)
Background: Most successful management of chronic disease patients depends on their follow-up. Type-2-diabetes mellitus (T2DM) patients who default their follow-up will receive minimal medical supervision. This will give an impact to the glycemic and lipid control achievement which finally will increase risk of complications. Objectives: To compare both glycemic and lipid profile control status in between T2DM defaulters and regular attendees at diabetes clinics. Methods: A prospective one-year study was conducted among T2DM from primary care clinics and DM-specialist clinic (hospital) in Kuantan. The research was conducted from July-2014 to Jun-2015. There were two follow-up appointments; at 6-month and 12-month within study period. Defaulter is defined as missing at least one occasion. Regular attendees were included as control group. Patients with missing records, known deceased cases and who are transferred out to other clinics were excluded. Investigation results of glycemic and lipid profile were collected at baseline (0-month) and after 1-year (12-month). Results: Of 405 diabetic patients, 18% (73/405) were defaulters. Lower percentage of defaulters came for blood investigations when compared to regular attendees (19%-26% vs 78%-88%) p<0.05. Target-achieved level in diabetic defaulters was lower then regular attendees in all blood parameters of fasting/random blood glucose (1.4% vs 23.4%); HbA1c (0% vs 11.4%); triglyceride (8.2% vs 48.5%); LDL-C (8.2% vs 35.0%) and HDL-C (5.5% vs 26.5%) with p<0.05. Conclusion: The study shows the defaulter rate is high among T2DM. They significantly contribute lower target-level achievement than regular attendees.